2001
DOI: 10.1177/002215540104900205
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Properties and Staining Behavior of Monodansylpentane, a Structural Homologue of the Lysosomotropic Agent Monodansylcadaverine

Abstract: S U M M A R YWe have recently shown that monodansylcadaverine labels autophagic vacuoles. Analysis of the mechanism underlying the labeling revealed that monodansylcadaverine acts as a lysosomotropic agent, being concentrated into acidic compartments by an iontrapping mechanism, and as a solvent polarity probe, increasing its relative fluorescence intensity by interacting with membrane lipids that are highly concentrated in the autophagic vacuoles. In this study, we synthesized three structurally related deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 15 publications
0
44
0
1
Order By: Relevance
“…The pattern of MDH puncta suggested that it is loading into (or forming) very lipid rich environments. 21 Indeed, when we examined MDH staining in superior cervical ganglion neurons induced to accumulate lipid droplets, MDH staining corresponded to the staining seen with the lipophilic dye Oil-Red O (data not shown). Thus, MDH too is unlikely to be useful as a marker of nascent autophagosome formation.…”
Section: Egfp-cd63 Marks Late Endosomes and Lysosomes But Not Early Ementioning
confidence: 71%
See 3 more Smart Citations
“…The pattern of MDH puncta suggested that it is loading into (or forming) very lipid rich environments. 21 Indeed, when we examined MDH staining in superior cervical ganglion neurons induced to accumulate lipid droplets, MDH staining corresponded to the staining seen with the lipophilic dye Oil-Red O (data not shown). Thus, MDH too is unlikely to be useful as a marker of nascent autophagosome formation.…”
Section: Egfp-cd63 Marks Late Endosomes and Lysosomes But Not Early Ementioning
confidence: 71%
“…Monodansylpentane (MDH) was synthesized as described previously. 21 pEGFP-LC3 was a kind gift of Tamotsu Yoshimori (National Institute for Basic Biology, Okazaki, Japan), pEGFP-CD63 was a kind gift of Paul Luzio (CIMR, University of Cambridge, UK), mRFP, kindly supplied by Roger Tsien (UCSD, Ca, USA) 37 was inserted in place of EGFP in the pEGFP-LC3 vector to create mRFP-LC3. The anti-LC3 antibody was a kind gift of Yasuo Uchiyama (Osaka University, Osaka, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, during 7KC-induced apoptosis, these cytoplasmic structures, which were previously described to produce positive staining with monodansylcadaverine (a solvent polarity probe and a lysosomotropic agent that stains acidic compartments) (13,23,33,60,61), were characterized by flow cytometric and microscopic methods including FRET biphoton spectral imaging confocal microscopy and by subcellular fractionation, gas chromatography, and mass spectrometry after staining with NR.…”
Section: Discussionmentioning
confidence: 99%